A9.18 Potential Therapeutic Application of Human Umbilical Cord wharton Jelly Derived Mesenchymal Stem Cells in Primary Sjögren's Syndrome. (25th February 2013) - Alunno, Alessia; Montanucci, Pia; Caterbi, Sara; Bistoni, Onelia; Basta, Giuseppe; Bartoloni, Elena; Pescara, Teresa; Pennoni, Ilaria; Calafiore, Riccardo; Gerli, Roberto
Abstract : Background and Objectives: hUCMS are adult stem cells easy to retrieve in bulk, under acceptable ethical conditions. Their immune-modulatory and pro-differentiation properties have been widely demonstrated. Modulation of the immune system is mediated by both cell contact and soluble factors such as interferon (IFN)-γ produced by hUCMS. Very few evidence is currently available with respect to potential therapeutic application of hUCMS in systemic autoimmune disorders. In particular, no data have been published in primary Sjögren's syndrome (pSS) to date. Furthermore, we have recently developed an endotoxin-free alginate matrix which can be used to microencapsulate (CpS) different cell types and transfer them into a non-immunosuppressed host. These microcapsules containing pancreatic islets, upon approval by the Italian Ministry of Health for in vivo use, have been grafted into a cohort of patients with type 1 diabetes mellitus with no adverse effects, while proving to be immunoprotective. On this background, we aimed to assess the in vitro immune system modulation by IFN-γ pretreated CpS-hUCMS on T cells from pSS, with special regard to Th17- and Treg-cell subsets. Materials and Methods: Ten pSS patients and 5 healthy donors (HD) were enrolled. Peripheral blood mononuclear cells (PBMC) were obtained by density gradient from heparinised venous blood. Co-cultures of CpS-hUCMS and PBMCs were arranged at different ratios. Lymphocyte proliferation was assessed by CFSE dilution assay. Phenotypic analysis by flow cytometry for regulatory and effector T cell subpopulations was performed after culture. Real time PCR analysis and the evaluation of culture supernatants for cytokine expression are currently ongoing. Results: CpS-hUCMS were able to inhibit HD and pSS PBMC cell proliferation and this effect was inversely correlated to hUCMS number. Phenotypic analysis revealed a predominant Th17-cell response in SS which was promptly hampered by CpS-hUCMS Moreover, Th1-cell proliferation was fair and reduced Cps-hUCMS FoxP3 and IL-17 expression among CD4 + T cells was also modulated by CpS-hUCMS, thereby suggesting that a Treg/Th17 rebalance. Conclusions: This is the first study evaluating the effects of hUCMSS on T cells in pSS. It appeared that CpS-hUCMS rebalance Treg/Th17 ratio and therefore may exert therapeutic effects in such disease. Furthermore, it is the first study that employs a new technology of drug delivery which may be applied in vivo in pSS patients.